Biodegradable intramedullary nail (BIN) with high-strength bioceramics for bone fracture. Issue 4 (6th January 2021) - Sun, Miao; Shao, Huifeng; Xu, Haibin; Yang, Xiaofu; Dong, Mingyi; Gong, Jiaxing; Yu, Mengfei; Gou, Zhongru; He, Yong; Liu, An; Wang, Huiming
Abstract : A novel biodegradable high-strength intramedullary nail (BIN) can affect the bone marrow microenvironment and benefit osteogenesis in vitro and in vivo . Abstract : About 10 million fractures occur worldwide each year, of which more than 60% are long bone fractures. It is generally agreed that intramedullary nails have significant advantages in rigid fracture fixation. Metal intramedullary nails (INs) can provide strong support but a stress shielding effect can occur that results in nonunion healing in clinic. Nondegradable metals also need to be removed by a second operation. Could INs be biodegradable and used to overcome this issue? As current degradable biomaterials always suffer from low strength and cannot be used in Ins, herein, we report a novel device consisting of biodegradable IN (BIN) made for the first time with bioceramics. These BINs have an extremely high bending strength and stable internal and external structure. Experiments show that the BINs could not only fix and support the tibial fracture model, but also promote osteogenesis and affect the microenvironment of the bone marrow cavity. Therefore, they could be expected to replace traditional metal IN and become a more effective treatment option for tibial fractures.